先化简,再求值:(m-n)•(m+n)+(m+n)的平方-2m的平方,其中m=1,n=-2

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/13 20:26:33
先化简,再求值:(m-n)•(m+n)+(m+n)的平方-2m的平方,其中m=1,n=-2
xPJ@~BI,!hIE.A_ c*{[(OHŇ1}'?[rzڙofq_q7g%S+>Q|@ S^OOj.G+t[["^dܙ:nMO=f{t]T(WYRx:5sW(PVȵ/3ݲ&H_UиG|XVkxM0ʖL"1|>?כ &̢@^oD5A?g

先化简,再求值:(m-n)•(m+n)+(m+n)的平方-2m的平方,其中m=1,n=-2
先化简,再求值:(m-n)•(m+n)+(m+n)的平方-2m的平方,其中m=1,n=-2

先化简,再求值:(m-n)•(m+n)+(m+n)的平方-2m的平方,其中m=1,n=-2
当m=1,n=-2时:
(m-n)•(m+n)+(m+n)的平方-2m的平方
=(m+n)2m-2m²
=2mn
=-4

m'2-n'2+m'2+2mn+n'2-2m'2=2mn
其中m=1,n=-2;
故原式=-4
求采纳。不懂可以追问。

原式=(m+n)(m-n+m+n)-2m^2
=2m(m+n)-2m^2
=2m(m+n-m)
=2mn
=2*1*(-2)
=-4